Pelatihan Kebersihan Destinasi Wisata Bagi Kelompok Sadar Wisata Di Kabupaten Klungkung - Kusumawati, I Gusti Ayu Wita; Yogeswara, Ida Bagus Agung (Jurnal Abdimas Perbanas, 2024)
The unpleasantness of tourists visiting a tourist destination can be caused by the cleanliness of the tourist destination area that is sometime ignored by the caretakers. Tourist destinations that are not kept clean can also cause diseases. Tourist destination managers play an important role in recreating a clean tourist destination. This community service activity was carried out to improve the knowledge of tourism awareness groups that operate tourist destinations in Klungkung Regency. This activity was carried out using course, discussion as well as workshop methods. After the course, the knowledge about the management and application of cleanliness in tourist destinations has showed some improvement. Through this activity, it is hoped that the partners can implement cleanliness in tourist destinations and give contribution to the increase of tourists visiting the tourist destinations.